Contemporary perspectives on research in creativity in early childhood education - Saracho, Olivia N. (Contemporary perspectives on research in early childhood education., 2012)
Recently, a new understanding of creative thought and creative performance has surfaced. It has also attracted the attention of early childhood professional organizations and researchers. Professional organizations have included it in their publications and conferences. While current creativity researchers have initiated a far more sophisticated understanding of young children's creative thinking, ways to assess creativity, strategies to promote creativity, and research methodologies.The purpose of this volume is to present a wide range of different theories and areas in the study of creativity to help researchers and theorists work toward the development of different perspectives on creativity with young children. It focuses on critical analyses and reviews of the literature on topics related to creativity research, development, theories, and practices. It will serve as a reference for early childhood education researchers, scholars, academics, general educators, teacher educators, teachers, graduate students, and scientists to stimulate further "dialogue" on ways to enhance creativity. The chapters are of high quality and provide scholarly analyses of research studies that capture the full range of approaches to the study of creativity --- behavioral, clinical, cognitive, cross-cultural, developmental, educational, genetic, organizational, psychoanalytic, psychometric, and social. Interdisciplinary research is also included, as is research within specific domains such as art and science, as well as on critical issues (e.g., aesthetics, genius, imagery, imagination, insight, intuition, metaphor, play, problem finding and solving). Thus, it offers critical analyses on reviews of research in a form that are useful to early childhood researchers, scholars, educators, and graduate students. It also places the current research in its historical context. The volume is also of interest to the general readers who are interested in the young children's creativity. The chapters are authored by established scholars in the field of young children's creativity.